78 Development of a Multifactorial Assessment of Dizziness for Middle-Aged and Older People. (20th December 2019) - Menant, Jasmine; Meinrath, Daniela; Sturnieks, Daina; Migliaccio, Americo; Close, Jacqueline; Lord, Stephen; Delbaere, Kim; Titov, Nickolai
Abstract: Background: More than 10% of people aged 50 years and older report dizziness. Despite available treatments, dizziness remains unresolved for many people due in part to sub-optimal assessment. Aims: to identify factors associated with dizziness handicap in middle-aged and older people to identify targets for intervention to address this debilitating problem. Methods: This secondary analysis of baseline and prospective data from a randomised-controlled trial involved 305 individuals aged 50-92 years reporting significant dizziness in the past year. Participants were classified as having either mild or no dizziness handicap (score < 31) or moderate / severe dizziness handicap (score: 31-100) based on the dizziness handicap inventory (DHI). Participants completed health questionnaires and underwent assessments of psychological well-being, lying and standing blood pressure, vestibular function, strength, vision, proprioception, processing speed, balance, stepping and gait. Participants also reported dizziness episodes in monthly diaries for 6 months following baseline assessment. Participants reported dizziness episodes in monthly diaries for six months following baseline assessment. Results: DHI scores ranged from 0-86 with 95 participants (31%) reporting moderate/severe dizziness handicap. Binary logisitic regression identified a postive Dix-Hallpike test for benign paroxysmal positional vertigo, cardiovascular medicationuse, high postural sway when standing on the floor with eyes closed and severe anxiety, as significant and independent predictors of moderate.severe dizziness handicap. Poor balance (high sway) also significantly identified participants who reported frequent (> or = weekly, n=134) dizziness episodes. Conclusion: Assessment of cardiovascular medication use, benign paroxysmal positional vertigo, anxiety and postural sway identify middle aged and older people with significant dizziness handicap. A multifactorial assessment including these facotrs may assist in tailoring evidence-based therapies to alleviate dizziness handicap in this group.